PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. POS INDONESIA REGIONAL X MAKASSAR - Ariza Zalzah Nurdin; Ikhwan Maulana Haeruddin; Chalid Imran Musa; Agung Widhi Kurniawan; Zainal Ruma (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This study attempts to evaluate how employees' job satisfaction is impacted by their workplace environment at PT Pos Indonesia Regional X Makassar. It adopts a quantitative approach, collecting data from a sample of 65 people using questionnaires, and then analyzing that data using the simple linear regression method using SPSS software. The work environment variable has a significant level of significance in the results, with a shockingly low p-value of 0.000 (far lower than the conventional cutoff of 0.05). Additionally, the dependent variable is significantly and favorably influenced by variable X, as indicated by its coefficient value of 0.596. This study supports the null hypothesis (H), showing that the workplace has a significant and advantageous impact on job satisfaction. According to this study, which is backed up by strong statistical data, the workplace culture at PT Pos Indonesia Regional X Makassar plays a crucial role in impacting employee job satisfaction.